Hydrogen enhanced cracking studies on Fe-3wt%Si single and bi-crystal microcantilevers - Hajilou, T.; Deng, Y.; Kheradmand, N.; Barnoush, Afrooz (The Royal Society Publishing, 2017)
© 2017 The Author(s) Published by the Royal Society. All rights reserved. Hydrogen (H) enhanced cracking was studied in Fe-3wt%Si by means of in situ electrochemical microcantilever bending test. It was clearly shown that the presence of H causes hydrogen embrittlement (HE) by triggering crack initiation and propagation at the notch where stress concentration is existing. Additionally, the effect of carbon content and the presence of a grain boundary (GB) in the cantilever were studied. It was shown that in the presence of H the effect of carbon atom on pinning the dislocations is reduced. On the other hand, the presence of a GB, while the chemical composition of material kept constant, will promote the HE. Crack initiation and propagation occur in the presence of H, while the notch blunting was observed for both single and bicrystalline beams bent in air. Post-mortem analysis of the crack propagation path showed that a transition from transgranular fracture to intragranular fracture mechanism is highly dependent on the position of the stress concentration relative to the GB.